Description of two new species of Meharia Chrétien, 1915 (Lepidoptera: Cossidae) from East Africa - Yakovlev, Roman; Ivinskis, Povilas; Rimsaite, Jolanta; Saldaitis, Aidas (Zootaxa, 2013)
The genus Meharia Chrétien, 1915 is a monotypic genus in the subfamily Mehariinae (Yakovlev 2011), clearly differentiated from other taxa in the family Cossidae. The morphological features of the genus are described in detail by Komarov and Zolotuhin (2005), Borth et al. 2011, Saldaitis and Ivinskis (2010) and Yakovlev (2011). Two unknown species of Meharia were collected in Kenya and Malawi and we describe them herein as new. The new species are similar to Meharia acuta Wiltshire 1982 and are distributed in the Arabian Peninsula (Hacker 1999; Yakovlev 2011). All three species have specific tineoid appearance and labial palpi twice as long as the head diameter. Currently, including the two newly described species, the genus Meharia consists of 13 species (Hacker 1999; Hacker et al. 1999, 2001; Yakovlev and Saldaitis 2008; Yakovlev 2011): M. acuta Wiltshire (distributed in Saudi Arabia, Yemen and Oman); M. avicenna Yakovlev (distr. in S Iran); M. fischeri Yakovlev & Saldaitis (distr. in Morocco); M. hackeri Saldaitis, Ivinskis & Yakovlev (distr. on Socotra Island, Yemen); M. incurvariella Chrétien (distr. in Algeria and Morocco); M. murphyi Yakovlev & Saldaitis sp. nov. (distr. in Malawi); M. ostrauskasi Ivinskis & Saldaitis sp. nov. (distr. in Kenya); M. philbyi Bradley (distr. across the Arabian peninsula in Saudi Arabia, Yemen and Oman); M. scythica Komarov et Zolotuhin (distr. in the S Volga region, SW Russia: ); M. semilactea (Warren et Rothschild) (distr. in Israel, Jordan, Saudi Arabia, Oman, UAE, Yemen, the Sinai Peninsula, Egypt, N Sudan, Morocco and Mauritania); M. tancredii Sutton (distr. in N. Iran); M. tanganyikae Bradley (distr. in Tanzania); M. yakovlevi Saldaitis & Ivinskis (distr. on Socotra Island, Yemen).